Medullary tuberculosis mimicking a multiple schwannoma - Mèhomè Wilfried Dossou; Wilfried Innocent Munkado Meuga; Ibrahim Issa Assoumane; Kpègnon Nicaise Agada; Laté Dzidoula Lawson; Konan Médard Kakou (Interdisciplinary Neurosurgery)
Background: Despite progress in the management of Tuberculosis (TB), it remains a major public health problem. Intramedullary tuberculosis is rare, and the rarity of this disease in the medullary cone makes preoperative diagnosis difficult. We report a case of intramedullary tuberculosis assimilated to a multiple schwannoma. Case presentation: A 14-year-old patient presented with a 7-month history of decreased hearing associated with micturition problems ranging from overflow voiding to acute urine retention 2 weeks ago. Clinical examination revealed right-sided hypoacusis and terminal cone syndrome. On paraclinical examination, audiometry showed conductive hearing loss on the right and a slight transmission loss on the left. A CT scan of the hip did not reveal any abnormality in the urinary tract. Thoracolumbar MRI showed a diffuse intramedullary lesion extending between T11 and L1, suggesting a low-grade glial lesion, particularly an astrocytoma or ependymoma. Given the auditory symptoms, the hypothesis of a multiple neuroma with cerebral and intramedullary localization was raised and a cerebral CT scan performed for this purpose came back normal. Tumour resection revealed a heterogeneous whitish process with a fleshy and soft necrotic portion. The pathological examination concluded that the tumor was tuberculous. The PCR came back negative and the patient was put on anti-tuberculosis treatment and corticosteroid therapy for 30 days. Progression was favorable, with progressive motor recovery from day 6 and complete recovery at day 60. Hearing loss persisted and was managed by ENT specialists. Conclusion: Intramedullary tuberculosis remains a reality. The insidious clinical picture and the atypical imaging appearance are factors in misdiagnosis. An effective meta-analysis would be timely to clarify the diagnostic presentation and allow agreement on the role of surgery in the face of chemotherapeutic measures.